Caracterização etnopedológica de áreas salinizadas no distrito de irrigação do Baixo Açu, polo fruticultor de Mossoró e Vale do Apodi - Silva, Jucirema Ferreira da (2021)
The identification and characterization studies of salinized areas can be developed using participatory methodologies for the construction of ethnopedological knowledge. The current research was developed in the Irrigated District of Baixo Açu, municipality of Alto do Rodrigues and Chapada do Apodi RN. Seven soil profiles were characterized by researchers (ethicist approach) and farmers (emicist approach), being identified as: P1 (area cultivated with bananas), P2 (fallow area) and P3 (area of native forest), in Irrigated District of Baixo Açu and four P1 (area cultivated with passion fruit), P2 (area of preserved forest), P3 (area cultivated with red rice) and P4 (area of native forest), in Chapada do Apodi RN. Deformed samples in the horizons, morphological, physical and chemical analysis were collected, according to classical methods. Attribute data were expressed as the average of three replications per horizon to determine the chemical analysis of saturation extract, sorting complex and soil granulometry. Afterwards, the data were submitted to multivariate analysis. Profile P1 was classified as CAMBISSOLO HÁPLICO Carbonático Solódico, P2 CAMBISSOLO HÁPLICO Ta Eutrófico Típico and P3 CHERNOSSOLO RÊNDZICO Órtico Saprolítico in Irrigated District of Baixo Açu and four soil profiles P1 and P2 were classified as LATOSSOLO VERMELHO AMARELO Eutrófico típico, P3 as VERTISSOLO HÁPLICO Sódico salino and P4 as VERTISSOLO HÁPLICO Órtico típico. Profiles P1 and P2 were considered sodium saline, P3 non-saline and Regarding the chemical attributes, there was an alkaline reaction in profiles P1, P2 and P3 and moderate acidity in P4. In the emic approach, the producers in their field of knowledge identified the studied areas with salt problems, through the precipitation of salts on the surface, change in leaf color and incidence of plants indicating saline areas. The perception of the producers regarding the accumulation of clay in the subsurface was called salão. The carbonate horizon was called larjão. P1 was classified as Terra de Salitre, P2 as Terra de Piçarro, and P3 Terra Boa without the presence of saltpeter. The classification carried out by farmers, compared with the classification of Sistema Brasileiro de Classificação de Solos, may present characteristics that are equivalent in terms of both classifications. The sand fraction was predominant in P1 and P2, being classified as sandy, associated with loose earth, without alloy, and P3 and P4 as alluvium, with the presence of cracks, being identified as Terra de Barro Preto com Salitre P3 and Terra de Barro Preto sem Salitre P4. Farmers perceive salinization of cultivated areas through visual observations regarding the diagnosis of leaves and precipitation of salt crystals on the surface. When salinization occurs in the subsurface, visual observations and leaf diagnosis are insufficient for the ethnopedological classification of areas with salt problems